The Scope of Government and its Impact on Economic Growth in OECD Countries - Bernhard Heitger (Kiel Institute of World Economics (IfW), 2001)
This paper investigates the relationship between the size of government and economic growth in OECD countries in 1960?2000. The underlying idea is that government expenditures on public goods basically have a positive effect on growth, but this growth effect tends to decline or even reverse when government is overdoing, e.g. by increasing expenditures in such a way that it ultimately also provides private goods. Empirical analyses based on panel estimates for 21 OECD countries support this hypothesis: Total government expenditures as well as expenditures by type indicate a significant negative impact on economic growth (excepting transfers and public investments).
Keywords: H1; H2; O4; 330; Government expenditure; taxation and economic growth; Staatsquote; Öffentliche Ausgaben; Wirtschaftswachstum; Schätzung; OECD-Staaten